IARS2 regulates proliferation, migration, and angiogenesis of human umbilical vein endothelial cells - Yu,Yue-ming (2021)
SUMMARY OBJECTIVE: In this study, we aimed at investigating the role of isoleucyl-tRNA synthetase in the growth, migration, and angiogenesis of human umbilical vein endothelial cells and the underlying molecular mechanism. METHODS: To assess the role of isoleucyl-tRNA synthetase, we silenced isoleucyl-tRNA synthetase in human umbilical vein endothelial cells using lentiviral 2 specific short hairpin RNAs (short hairpin RNAs 1 and 2) and examined silencing efficiency using real time quantitative polymerase chain reaction and western blot analyses. Short hairpin RNAs 1-isoleucyl-tRNA synthetase had greater knockdown efficiency, it was used in the entire downstream analysis. Short hairpin RNAs 1- isoleucyl-tRNA synthetase silencing effects on cell proliferation, cell colony generation, cell migration, as well as angiogenesis were assessed using cell counting kit-8, colony development, cell migration, and angiogenesis tube formation assays, respectively. RESULTS: Compared to the control group, anti-isoleucyl-tRNA synthetase short hairpin RNAs significantly silenced isoleucyl-tRNA synthetase expression in human umbilical vein endothelial cells, and suppressed their proliferation, migration, and angiogenic capacity. To characterize the underlying mechanism, western blot analyses showed that isoleucyl-tRNA synthetase knockdown suppressed phosphorylation of extracellular-regulated kinase ½ and protein-serine- threonine kinase, as well as expression of vascular endothelial growth factor, GSK-3β, and β-catenin. CONCLUSIONS: We have shown, for the first time, the critical role of isoleucyl-tRNA synthetase in human umbilical vein endothelial cells. Our data show that isoleucyl-tRNA synthetase knockdown suppresses human umbilical vein endothelial cell proliferation, migration, and angiogenesis. We have also shown that isoleucyl-tRNA synthetase knockdown suppresses phosphorylation of extracellular-regulated kinase ½ and protein-serine- threonine kinase, as well as expression of vascular endothelial growth factor, GSK-3β, and β-catenin. Together, these data highlight isoleucyl-tRNA synthetase as a potential antitumor anti-angiogenic target.